Banking Union of the European Union Member States (Economic and Political Thought, 2014)
As a result of the global financial crisis, the European Union countriessuffered deep recession. It turned out that the financial system, especiallythe European banking sector, is not resistant to the influence of such eventsmainly because of imperfect financial architecture. Undertaken measuresaimed at structural reforms and the establishment of a banking union. Whilestructural reforms of the banking sector covered all the European Unioncountries, the banking union will affect only the Eurozone countries andthose remaining ones that express the will to participate in the new financialarchitecture. It will constitute a good basis for undertaking further strongintegration steps in Europe.